Habitat use by yellow-footed rock-wallabies in predator exclusion fences. (January 2021) - Smith, Deane; Allen, Benjamin L.
Abstract: Predator density changes can alter behaviours of prey, and removal of predators is expected to free prey from predation risks. Due to pest management activities within predator exclusion fences in central-western Queensland, Australia, dingoes ( Canis familiaris ) have been actively controlled in places also inhabited by endangered yellow-footed rock-wallabies (YFRW, Petrogale xanthopus ). These pest management practices are expected to enable YFRW to utilise otherwise riskier habitats, though the occurrence of these processes remain unclear. Here, we assessed the responses of YFRW habitat use to pest species management in exclusion fences. In congruence with previous work, we find the likelihood of YFRW presence is positively correlated with increasing habitat complexity (r = 0.39). Greater coverage of ground and shrub vegetation also correlated positively with YFRW presence (p < 0.05). However, we found no difference in YFRW habitat selection inside and outside exclusion fences, which was considered to be an artefact of populations of predators still surviving inside the fence, along with insufficient elapsed time to adequately assess behavioural responses by YFRW since the construction of the fence. These results support the view that even small numbers of predators can have a limiting effect on threatened prey and/or that researchers must allow sufficient time to observe prey responses to changes in predation risk. Highlights: Yellow-footed rock-wallaby habitat use positively correlates to habitat complexity. Ground and shrub coverage also positively influenced rock-wallaby habitat use. Rock-wallabies habitat use did not differ on either side of an exclusion fence.